Le dilemme du Parti républicain dans le Wisconsin suite à l’élection de Trump - Roman Vinadia (Revue LISA)
The results of the 2016 presidential election seem to indicate the Republican Party’s completion of its conquest of rural America. Yet, those results hide significant voting patterns that point to a dilemma the Party will have to address if it is to maintain electoral viability. While very successful in rural places, Donald Trump has been rejected by conservative Republicans from the suburbs, who constitute the last important demographic area the Party could try to win to compete with the Democrats. More importantly, the addition of a new electoral base within Republican ranks threatens the rapprochement between the Republican Party and the conservative movement. Through a cartographic analysis, this article aims to show how the results of the 2016 election in Wisconsin illustrate this dilemma. The Republican Party is torn between the trumpian rural electorate and its traditional suburban conservative power centers.